Complementary action of ginger as bioenhancers in the treatment of diabetes - M, Ashoka Shenoy; Mahurkar, Nitin (Indian Journal of Pharmacy & Drug Studies, 2024)
Aim and objective: To evaluate the role of Zingiber officinale extract along with glibenclamide on lipid profile in alloxan & streptozotocin induced diabetes mellitus in rats. Method and Materials: The diabetes in rats was induced by the administration of intraperitoneal injection of alloxan (100mg/kg) and streptozotocin (65 mg/kg). After 2 days of injection, the hyperglycaemic rats (glucose level > 200 mg/dl) were separated and divided into five groups consisting of six rats in each group. The oral treatment was started from the same day for next three weeks. On 21st day the blood was collected for biochemical estimations by retro orbital puncture. The serum was obtained by centrifuging the blood samples at 3000 rpm for 10 m and used for estimation of SGPT, SGOT, SOD and CAT. Results: Diabetic rats treated with glibenclamide and glibenclamide along with ginger extract showed significant (p<0.001) reduction in the elevated levels of total cholesterol, triglycerides and LDL cholesterol in comparison to diabetic control group. The effect was less significant in rats treated with only ginger extract (p<0.01). Also, the HDL level was significantly (p<0.001) increased in glibenclamide and glibenclamide along with ginger treated group. Serum biomarkers such as SGPT and SGOT level were significantly elevated in diabetic control group. The animals treated with glibenclamide and glibenclamide in combination with ginger extract, the elevated SGPT and SGOT levels were normalised significantly (p < 0.001, p < 0.01 respectively) as compared to the diabetic control. From antioxidant studies, it was found that alloxan and streptozotocin induced diabetic control animals showed a significant decrease in the levels of SOD and CAT as compared to normal control. The animals treated with glibenclamide and glibenclamide + ginger extract combination showed significant increase in CAT and SOD (p<0.01 and p<0.001 respectively) as compared to diabetic control. Conclusions: The findings of the study suggest that, ginger shows complementary action with glibenclamide in the treatment of diabetes. So it can be considered as a safe supplementary in management of diabetes mellitus. Further studies has to conducted, to check whether dosage of glibenclamide can be reduced when it is given along with ginger.